CULTURAL VALUE OF THE MEANING OF POLITENESS IN LINGUISTICS - Tojibayeva Farida Yusufjanovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation. Politeness, a fundamental aspect of human interaction, varies significantly across cultures, reflecting deeply ingrained societal norms and values. This article investigates the cultural significance of politeness in linguistics, employing an interdisciplinary approach to unravel its multifaceted nature. Through a comprehensive literature analysis, methods of politeness expression are examined, followed by an exploration of the results obtained from cross-cultural studies. The discussion delves into the implications of these findings, offering insights into the complex interplay between language, culture, and politeness. Conclusions drawn highlight the importance of cultural sensitivity in communication and suggest avenues for further research.